Experimental study of bullet holes on aluminium targets fired with 9mm pistol and 9mm submachine gun (SMG) at varying distances - Muhammad Hazeeq,; T. Nataraja Moorthy,; Rasyidi Harun,; Mohd Zahedi Daud, (Malaysian Society of Applied Biology, 2016)
All the guns have their own unique identifying features and even if the gun has not been left at the crime scene many degrees of information can be determined from the bullet, bullet holes on the targets, the nature of the wound and any residue that is left around it. Researchers have conducted studies about the evaluation and reconstruction of fired bullet paths delivered in indoor scenes and their performance in a unique environment. Bullet performance is typically a function of the matrix in which the bullet interacts. The identification of bullet holes is based, besides the morphology of the hole in question, on the presence of gunshot residue and of blackening in the vicinity of the hole. It is shown that field tests were conducted by police agencies and researchers to discover the relationship between bullet holes on different types of targets and firearms. The present study was aimed to conduct an experimental study of bullet holes on aluminium targets fired with 9 mm pistol and 9 mm submachine gun with varying distances which formed a database for forensic application. The shooting exercise was conducted at Sungai Buloh shooting range by trained firearm experts, Polis Di Raja Malaysia, Bukit Aman, Kuala Lumpur.